Designing a Patient-Centric PRM Model in Healthcare E-Commerce: Insights from Doctors and Patients in Tbilisi, Georgia - (PhD, DBA), Dr. Bahman Moghimi; (MD), Dr. Soroush Monemizadeh (South Eastern European Journal of Public Health, 2025)
The digital revolution in healthcare has driven Patient Relationship Management (PRM) systems to the forefront of patient-centred care, emphasizing personalization, efficiency, and data-driven insights. However, their implementation in transitional economies like Georgia faces significant challenges due to fragmented systems, limited infrastructure, and evolving patient expectations. This study develops an innovative PRM model tailored to Georgia, focusing on real-time insights, telemedicine integration, predictive analytics, and mobile health platforms.Using a mixed-methods approach, the research identifies critical unmet needs of doctors and patients while validating the model through advanced statistical analysis. The findings demonstrate the potential of advanced PRM functionalities to enhance patient satisfaction, operational efficiency, and care delivery. The proposed model offers scalable solutions for transitional healthcare systems, setting a foundation for future innovations in digital healthcare globally.